2021
DOI: 10.3390/plants10040790
|View full text |Cite
|
Sign up to set email alerts
|

Phytostimulatory Influence of Comamonas testosteroni and Silver Nanoparticles on Linum usitatissimum L. under Salinity Stress

Abstract: They were shifting in land use increases salinity stress, significant abiotic stress affecting plant growth, limiting crop productivity. This work aimed to improve Linum usitatissimum L. (linseed) growth under salinity using Comamonas testosteroni and silver nanoparticles (AgNPs). AgNPs were fabricated exploiting Rosmarinus officinalis and monitored by U.V./Vis spectrophotometry scanning electron microscopy (SEM) and Fourier transforms infrared spectroscopy (FTIR). Photosynthetic pigments, enzymatic and nonenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 81 publications
2
7
0
Order By: Relevance
“…The increase in chlorophyll content at different salt concentrations raised corresponded with the results obtained by Singh, Sillu, Kumar, and Agnihotri (2021). Our results regarding a decrease in chlorophyll a and b, and total chlorophyll, agreed with the work reported by Khalofah, Kilany, and Migdadi (2021). Carotenoids content was observed to be decreased with salinity stress, supported by the studies of Jahangir, Javed, and Bano (2020).…”
Section: Discussionsupporting
confidence: 93%
“…The increase in chlorophyll content at different salt concentrations raised corresponded with the results obtained by Singh, Sillu, Kumar, and Agnihotri (2021). Our results regarding a decrease in chlorophyll a and b, and total chlorophyll, agreed with the work reported by Khalofah, Kilany, and Migdadi (2021). Carotenoids content was observed to be decreased with salinity stress, supported by the studies of Jahangir, Javed, and Bano (2020).…”
Section: Discussionsupporting
confidence: 93%
“…These are important as natural solutes that maintain cellular homeostasis and assist in cell osmoregulation under salinity stress. Similar to our findings, Khalofah et al 42 reported that NPs increased the amounts of proline and soluble sugars in linseed under salt stress. Abiotic types of stress such as salinity and drought caused excessive amounts of reactive oxygen species (ROS), which resulted in the vulnerability of proteins, DNA, and carbohydrates in plants.…”
Section: Discussionsupporting
confidence: 93%
“…The effect of biogenically generated AgNPs at appropriate concentrations on rice plant carotenoid and chlorophyll levels was explored by the authors of reference [ 76 ], and there was a considerable increase in their production. The authors of reference [ 77 ] investigated the effect of AgNPs on Linum usitatissimum L. and found that they were effective in raising carotenoid contents, and AgNPs showed a significant rise in chlorophyll concentration in recent research by the author of reference [ 78 ].…”
Section: Discussionmentioning
confidence: 99%